Multi-choice stochastic bi-level programming problem in cooperative nature via fuzzy programming approach - Sumit Kumar Maiti; Sankar Kumar Roy (Journal of Industrial Engineering International, 2016)
In this paper, a Multi-Choice Stochastic Bi-Level Programming Problem (MCSBLPP) is considered where all the parameters of constraints are followed by normal distribution. The cost coefficients of the objective functions are multi-choice types. At first, all the probabilistic constraints are transformed into deterministic constraints using stochastic programming approach. Further, a general transformation technique with the help of binary variables is used to transform the multi-choice type cost coefficients of the objective functions of Decision Makers(DMs). Then the transformed problem is considered as a deterministic multichoice bi-level programming problem. Finally, a numerical example is presented to illustrate the usefulness of the paper.
Keywords: 650; Bi-level programming; Stochastic programming; Multi-choice programming; Fuzzy programming; Non-linear programming